E Antigen-antibody system as indicator of liver damage in patients with hepatitis-B antigen. Issue 5991 (1st November 1975) - El Sheikh, N; Woolf, I L; Galbraith, R M; Eddleston, A L; Dymock, I W; Williams, R
Abstract : The clinical relevance of the e antigen-antibody system was investigated in 61 people persistently positive for hepatitis-B surface antigen, including 22 healthy carriers. The e antigen was not detectable in any of the healthy carriers, whereas it was found in 15 out of 28 patients with chronic aggressive hepatitis and two out of 11 with chronic persistent hepatitis. Its presence therefore indicates chronic liver disease but its absence does not exclude it. It may prove to be a particularly useful prognostic aid in chronic persistent hepatitis, since one of the two patients in whom it was found later developed aggressive hepatitis. In contrast, e antibody is of little diagnostic help, for, though it was found mostly in healthy carriers (18;82%), it was also detectable in 9 (23%) of the patients with chronic hepatitis. In 13 (76%) of the patients positive for e antigen Dane particles were seen on electron microscopy, but these were also present in 5 (19%) of the patients positive for e antibody. These findings are consistent with other evidence suggesting that e antigen is not a surface component of the Dane particle, but rather an independent soluble protein manufactured by the host in response to infection with the hepatitis-B virus.